1987
DOI: 10.1039/p29870001877
|View full text |Cite
|
Sign up to set email alerts
|

Lactone formation in superacidic media

Abstract: The reaction of substituted 1 -hydroxycyclohexanecarboxylic acids in fluorosulphuric acid has been studied. Cyclisation takes place around 0 "C, accompanied by rearrangement in appropriate cases, yielding the thermodynamically stable lactone or mixture of lactones. An unexpected feature of these reactions is that the carboxy-substituted cyclohexyl carbocation does not undergo ring contraction, unlike the unsubstituted cyclohexyl carbocation, although the cycloheptyl system contracts to cyclohexyl. We suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Whittaker and Carr have described a series of superacid-promoted reactions to prepare bicyclic lactones [ 28 ]. Several of the conversions involve superelectrophilic rearrangements.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Whittaker and Carr have described a series of superacid-promoted reactions to prepare bicyclic lactones [ 28 ]. Several of the conversions involve superelectrophilic rearrangements.…”
Section: Reviewmentioning
confidence: 99%
“…Several studies have examined this question using deuterium-labeled superelectrophiles. Reaction of 1-hydroxycyclohexanecarboxylic acid ( 137 ) in FSO 3 H and SO 3 at −70 °C, followed by warming to 0 °C, gives a clean conversion to the protonated bicyclic lactone 140 ( Scheme 28 ) [ 28 ]. A mechanism is proposed which involves ionization to the superelectrophile 138 , followed by successive hydride shifts to give the charge separated dication 139 .…”
Section: Reviewmentioning
confidence: 99%
“…(3.71)]. Protonated lactones may be prepared by direct protonation 582 or by protonating hyroxycarboxylic acids 583 [Eq. Experimental evidence and theoretical data indicated that the strained cubyl system effectively stabilizes the carbocationic centers through CÀC bond hyperconjugation (283).…”
Section: Trivalent Carbocationsmentioning
confidence: 99%